Recent Research in Black Sea Region on Motivation in Education (Review) - DOGHONADZE, Natela; FEDORCHUK, Iryna (Journal of Education in Black Sea Region, 2016)
Motivation in education - that of administrators, teachers and especially students - has always been one of essential preconditions of efficient learning and teaching. By itself it does not guarantee achievement, especially measures by testing and grades, but it created a good background for efficient learning. And vice versa, lack of motivation usually has a negative impact of achievement. Various aspects of motivation have been researched, and the topic seems eternal and inexhaustible. This review presents some research that has been recently held in the Black Sea region countries concerning motivation in education.